2020
DOI: 10.1016/j.heliyon.2020.e04003
|View full text |Cite
|
Sign up to set email alerts
|

Providing organic food to urban consumers: case studies of supermarkets in Bangkok and metropolitan area

Abstract: This study aimed to 1) explore the information flow by which supermarkets attempt to communicate with consumers, and 2) make a preliminary evaluation of the strategies used by supermarkets to promote organic food to consumers specifically within the Bangkok Metropolitan Area. Nine supermarket outlets located at the headquarters of nine supermarket chains were observed. Eleven informants from four supermarket chains were interviewed. The results found that supermarkets in Thailand provided rich information abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In some cases, the consumption of organic products is even positively conditioned by the practice of prices that are significantly higher than those for conventional food [ 1 ]. In line with these assertions, some authors found that retailers should be very judicious in implementing discount policies on organic products, as this could lead to negative effects on sales [ 101 , 102 ].…”
Section: Discussionmentioning
confidence: 98%
“…In some cases, the consumption of organic products is even positively conditioned by the practice of prices that are significantly higher than those for conventional food [ 1 ]. In line with these assertions, some authors found that retailers should be very judicious in implementing discount policies on organic products, as this could lead to negative effects on sales [ 101 , 102 ].…”
Section: Discussionmentioning
confidence: 98%
“…Whereas in another study, which investigates gender-based behavioural pattern of GSO foods, women expressed greater interest in consuming fruits and vegetables mostly compared to men; and while both men and women agree that organic foods are produced in a sustainable manner, their high price, difficult access, irregular supply and availability in few establishments were highlighted as the main limiting factors for not consuming organic foods ( Martins et al, 2020 ). A similar study conducted in Spain and Thailand towards consumers' perception and attitude, as well as retailers’ attitude to GSO foods showed similar results, respectively, with cost being a premium factor ( Rodríguez-Bermúdez et al, 2020 ; Kantamaturapoj and Marshall, 2020 ). These studies showed that emotion, trust, gender differences, cost, access and availability are challenges associated with GSO foods and should be considered to formulate good smart policies.…”
Section: Challenges Associated With Gso Foodsmentioning
confidence: 54%
“…Product-level and retail-level communication help to build trust toward organic food [ 71 , 72 ], although Perić et al [ 73 ] disagree with it. According to them, 63% of Serbian and 50% of Croatian consumers do not believe advertisements on organic food, which derives from the general mistrust in the media and advertising.…”
Section: Resultsmentioning
confidence: 99%